Pentingnya Peduli Lingkungan terhadap Penanaman Nilai Karakter pada Siswa - Sunandari Sunandari; Mesyah Salsabilah; Ifa Aulia; M. Akhyar Armar (Departement of Mathematics Education, 2023)
The character value of caring for the environment in the world of education aims to make students have the knowledge and awareness that each individual has a role with the surrounding environment and can create change. This study aims to find out how to instill the character values of caring for the environment and responsibility in SD Inpres Tamalanrea 3 Makassar students. This research method uses descriptive research with a qualitative observational approach. The results of the study showed that by making direct observations about teachers instilling environmental care character education in class, in addition to direct observations, researchers also conducted interviews with teachers about teachers implementing environmental care character education values in class III SD Inpres Tamalanrea 3 Makassar.